Analysis Of Bacteria Escherichia Coli In Tembakul (Periophthalmus Schlosseri) From Coastal Waters In Kuala Enok District, Indragiri Hilir Regency Riau Province - Perie Anugraha Wiguna; Dessy Yoswaty; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in March 2014 in the coastal waters of the Village of Kuala Enok of Indragiri Hilir Regency in Riau Province. The purpose of this study was to determine the level of bacterial contamination of E. coli as an indicator of pollution on “tembakul” (P. schlosseri) fish in the coastal waters of Kuala Enok. Tembakul fish sampling conducted at three observation station, station I is located in the territorial waters adjacent to residential, station II is located in the creek waters, and station III is located in the open sea waters. Samples of “tembakul” fish were analyzed by using the MPN method three series tube at the Laboratory of Microbiology and Biotechnology of Fisheries and Marine Sciences Faculty of University of Riau. The yield on the analysis of the sample gills, digestive tract and fish meat tembakul showed that at the settlement waters and the creek waters the number of bacteria was 1,100 MPN/g but had differences on the meat at the open waters with an average of 747.67 MPN/g. The results showed that the innoculation of bacteria growing at the time of isolation was from the coliform group. Total coliform values ​​at each point of observation station was above the food quality and safety standards required by BSNI 7388: 2009 and BPOM (Agency for Food and Drug Administration) of the maximum contaminant limits in food is 10 MPN/g in fresh meat. Keywords: Coliform, Tembakul fish, Kuala Enok